2001
DOI: 10.1046/j.1365-2958.2001.02247.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the global regulator FlhD from Escherichia coli at 1.8 Å resolution

Abstract: SummaryFlhD is a 13.3 kDa transcriptional activator protein of flagellar genes and a global regulator. FlhD activates the transcription of class II operons in the flagellar regulon when complexed with a second protein FlhC (21.5 kDa). FlhD also regulates other expression systems in Escherichia coli. We are seeking to understand this plasticity of FlhD's DNA-binding specificity and, to this end, we have determined the crystal structure of the isolated FlhD protein. The structure was solved by substituting selen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 45 publications
4
37
0
Order By: Relevance
“…CheY and CheZ localization is dependent on CheA, and CheA localization is dependent on CheW. Similar localization studies using a CheZ-GFP fusion were reported by Brian Cantwell (M. (20). Two molecules of FlhD (gold and purple) form a tightly associated dimer which, when complexed with another protein, FlhC, activates transcription of flagellar genes.…”
Section: Signal Transduction In Chemotaxissupporting
confidence: 79%
See 1 more Smart Citation
“…CheY and CheZ localization is dependent on CheA, and CheA localization is dependent on CheW. Similar localization studies using a CheZ-GFP fusion were reported by Brian Cantwell (M. (20). Two molecules of FlhD (gold and purple) form a tightly associated dimer which, when complexed with another protein, FlhC, activates transcription of flagellar genes.…”
Section: Signal Transduction In Chemotaxissupporting
confidence: 79%
“…The first group consists exclusively of flhC and flhD, whose products form a heterotetramer that is required for the synthesis of subsequent classes of flagellar components. Andres Campos and colleagues (P. Matsumura's lab) described the crystal structure of the FlhD homodimer at 1.8-Å resolution (20) (Fig. 4C).…”
Section: Transcriptional Regulation Assembly and Structure Of Flagementioning
confidence: 99%
“…Since the amount of FlhC protein in the lrp mutant was not increased by butyrate, it is unlikely that SCFAs affect the stability of FlhC and FlhD proteins. One possible mechanism is that SCFAs affect FlhD 4 FlhC 2 activity by changing disulfide bond formation (2) or zinc binding (32) or through an unknown modification. The response to SCFAs via the class II promoter seems to be important for the induction of flagellar gene expression in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of FliT on degradation of individual FlhC by ClpXP in vitro was not determined because the FlhC subunit could not be purified as a soluble protein, whereas FlhC could be purified when complexed in FlhD 4 C 2 . Purification of individual FlhC has so far not been successful (27,28).…”
Section: Flhd 4 C 2 Inhibition By Flit Is Partially Suppressed In Clpxpmentioning
confidence: 99%